WOMEN’S LANGUAGE FEATURES USED BY ENGLISH TEACHER CANDIDATES - Elisabeth Wulan Wahyuningtyas (ELTR Journal, 2018)
This paper discussed women’s language features used by female students in English Language Education Study Program (ELESP) as English teacher within teaching learning practices in micro-teaching class. The study aimed to investigate the frequency of the women’s language features and the possible reason of using the features by female students. The writer assumed that women have characteristics in speaking, including female English teacher candidates. Unconsciously, female English teacher candidates use some or all of women’s language features when they are doing teaching practice in Micro Teaching class. These features indicate that actually, if a woman or a female English teacher candidate uses most of the features, that she is not really sure about what she is uttering to the pupils in English learning activities. Besides that, a teacher should be confident in delivering materials or teaching the pupils. Those features have been discussed by Robin Lakoff in one of her books entitled Language and Woman’s place. In that book, she writes about ten language features which are usually used by the women when they are speaking. Therefore, it encouraged the writer to conduct a paper about women’s language used by female students in ELESP as English teacher candidates.